Determining the Role of Neutrophil-Lymphocyte Ratio in Ascertaining the Outcomes of Preterm Premature Rupture of Membranes - Vemulapalli, Lakshmi Sravani (Issues and Developments in Medicine and Medical Research Vol. 10, 2022)
Background: Premature Rupture of Membranes (PROM) is a serious obstetric issue. The neutorphil-lymphocyte ratio (NLR) is expected to shed light on the potential scope of early PROM prediction. With this as a backdrop, the current study was conducted to compare NLR among preterm PROM and healthy controls in order to assess the predictive role of NLR and platelet-lymphocyte ratio (PLR). Methods: This case control study included 101 pregnant women (44 pregnant women diagnosed with Preterm PROM and 55 term gestation matched healthy controls). Laboratory parameters were measured, including a complete blood count. PLR was calculated by dividing the number of platelets by the lymphocyte count, and NLR was calculated by dividing the neutrophil count by the lymphocyte count from the same blood samples. Results: When compared to controls, all inflammatory markers, including total count, neutrophil count, NLR and PLR ratios, were elevated in the PPROM group. The observed differences in these parameters' mean levels were statistically significant (p<0.05). Conclusion: Monitoring NLR during the second and early third trimesters as a routine practise among high risk mothers may be considered to aid in the early prediction of PPROM and the reduction of adverse maternal and neonatal outcomes.